Preservación digital y bibliotecas: un nuevo escenario - Orera Orera, Luisa (Revista General de Información y Documentación, 2009)
The article tackles the question of digital preservation and analyses some significant initiatives carried out in the field, such as the Charter on the Preservation of Digital Heritage, the Guidelines for the preservation of Digital Heritage, and other national and international projects. Through the analysis of these projects, it is demonstrated that libraries are bound to perform an important role in the preservation of the digital patrimony of their respective countries. Compared with the preservation of traditional documents, digital preservation requires changes in the updating of libraries. Clearly, the most important among these changes are the need for the universities to cooperate both among themselves and with other institutions related to information management.
Keywords: Digital Preservation; Digital Heritage; Charter on the Preservation of Digital Heritage; Guidelines for the preservation of Digital Heritage; UNESCO; National Library of Australia; National Library of France; Library of Catalonia